OPTIMALISASI RUTE DISTRIBUSI MENGGUNAKAN METODE TRAVELING SALESMAN PROBLEM (TSP) UNTUK MEMINIMASI BIAYA DISTRIBUSI - hilmy oktorio zupemungkas; Wiwik Handayani (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
As the company is growing, it is faced with increasing distribution costs due to various distribution purposes. This research aims to know the optimal distribution route to minimize company distribution costs. It also aims to know the distribution factors that affect the efficiency of the results obtained at GO Sumber Plastik. Traveling salesman problem with Branch and Bound algorithm is one of the methods to be used to select the most optimal route by WinQSB software. The company has two fleets with different fuel types (petalite and biodiesel fuel) for two different trips each day. There are two trips as long trips and short trips. However, Sunday is only available for one trip. There are two alternatives for the research result. Alternative 1 produces efficiency for 7% and alternative 2 produces efficiency for 11%. However, there are distribution factors that can affect the efficiency of distribution costs. The researcher needs to provide advice from company external experts who are experienced in their fields to overcome those factors. Those factors are area space, internal infrastructures, weather, general traffic jam, and culture.